2021
DOI: 10.1016/j.ymthe.2021.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Correction of a urea cycle defect after ex vivo gene editing of human hepatocytes

Abstract: Ornithine transcarbamylase deficiency (OTCD) is a monogenic disease of ammonia metabolism in hepatocytes. Severe disease is frequently treated by orthotopic liver transplantation. An attractive approach is the correction of a patient's own cells to regenerate the liver with gene-repaired hepatocytes. This study investigates the efficacy and safety of ex vivo correction of primary human hepatocytes. Hepatocytes isolated from an OTCD patient were genetically corrected ex vivo, through the deletion of a mutant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…demonstrated the transplantation of patient-derived donor human hepatocytes into FRGN mice to generate a humanized model of ornithine transcarbamylase deficiency. 39 The weakness of this approach is that the chimeric humanized-liver FRGN mice are immune compromised, which limits the type of experiments that can be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated the transplantation of patient-derived donor human hepatocytes into FRGN mice to generate a humanized model of ornithine transcarbamylase deficiency. 39 The weakness of this approach is that the chimeric humanized-liver FRGN mice are immune compromised, which limits the type of experiments that can be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Primary human hepatocytes were electroporated using modified procedures described in Zabulica et al . 39 Briefly, hepatocytes were electroporated with P3 Primary Cell 4D-Nucleofector solution (Lonza), program CA-137, and the following electroporation conditions: 100 μL P3 nucleofection buffer, 1.8 μL of 20 μg/μL sgRNA, 5 μL of 61 μM V3 SpCas9 (product code: 1081059; Integrated DNA Technologies) or 5 μL of 61 μM V3 HiFi SpCas9 (product code: 1081061; Integrated DNA Technologies), and 3 μL of 100 μM Electroporation Enhancer (product code: 1075916; Integrated DNA Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Generation of Genome-Edited HepG2 GPR35 KO Cells. Expression of full-length mRNA from the GPR35 gene was eliminated using a dual synthetic gRNA/RNP approach 43 with one guide cutting the intron and one in the exon region to generate a nonfunctional GPR35 protein. The gRNAs were designed with the CRISPR Finder (Welcome Sanger Institute).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Two major roadblocks that have limited clinical progress with hepatocyte transplantation are the lack of renewable high-quality human hepatocyte sources and the inability to efficiently correct inborn errors in PHHs. In this issue of Molecular Therapy, Zabulica et al 3 show the first genetic correction of an inborn error in PHHs.…”
mentioning
confidence: 99%
“…Ornithine transcarbamylase (OTC) deficiency is a rare X-linked disorder of the urea cycle, resulting in ammonia elevation with life-threatening neurological complications. Zabulica et al 3 identified a splice acceptor site variant that results in an early stop codon and dysfunctional protein in an OTC patient who underwent liver transplantation. Using synthetic guide RNA and recombinant Cas9 ribonucleoprotein complex transfection, the authors were able to remove the splice variant in 60%-80% of PHHs isolated from the explanted liver and restore OTC function.…”
mentioning
confidence: 99%